Transparency and Accountability in the Digital Era: Insights from Public Sector Accounting - Lestari, Putri Ayu (Yayasan Sinergi Kawula Muda, 2025)
This study presents a narrative review examining how digital transformation reshapes public sector accounting by synthesizing recent literature on its opportunities, challenges, and policy implications. The review aims to analyze the transition from manual to digital and data-driven systems using a structured and integrative approach. Literature from Scopus and Web of Science was reviewed through targeted keywords—digital transformation, e-government, and public sector accounting—focusing on peer-reviewed studies published between 2010 and 2024 to ensure quality and relevance. Findings reveal that digital accounting systems enhance operational efficiency and reduce fraud risks, while e-government platforms improve transparency and citizen engagement by increasing access to financial data. The integration of big data analytics and forensic accounting strengthens auditing and oversight, though implementation success largely depends on infrastructure readiness and institutional support. Human capital emerges as a decisive factor, as digital literacy gaps among accountants and auditors hinder effective adoption. Persistent challenges include organizational resistance, limited resources, and data security risks across regions. Drawing on institutional theory, the discussion highlights how structural and cultural factors influence adoption patterns and outcomes. The study concludes that the transformative potential of digitalization in public sector accounting can only be realized through comprehensive strategies integrating technological investment, capacity building, and supportive policy frameworks. Future research should explore longitudinal and cross-regional analyses to deepen understanding of digital transformation’s long-term impacts on governance and accountability.